2009
DOI: 10.1002/chem.200802036
|View full text |Cite
|
Sign up to set email alerts
|

On the Initiation Mechanism of Syndiospecific Styrene Polymerization Catalyzed by Single‐Component ansa‐Lanthanidocenes

Abstract: The mechanism of the initiation step of styrene polymerization promoted by single-component ansa-lanthanidocene catalysts [{Cp'XMe(2)Flu'}Ln(R)(ether)(n)] (Cp' = C(5)H(4); Flu' = 9-C(13)H(8); X = C or Si; R = allyl = CH(2)CHCH(2) or alkyl = CH(2)SiMe(3); ether = THF or Et(2)O, n = 0,1) has been studied from a combined experimental/theoretical perspective. First, detailed (13)C NMR studies conducted on syndiotactic oligostyrenes prepared by chain-growth polymerization with [{C(5)H(4)CMe(2)Flu'}Nd(eta(3)-1,3-C(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…From a mechanistic viewpoint, it should be noted that the mono‐ or diene insertion into the π‐allyl system of [La]( syn ‐η 3 ‐C 4 H 7 ) occurs directly and in a concerted way. There is no need to form an intermediate σ‐allyl complex;15 this was also reported by Tobisch for Ti‐based catalysts 12c…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…From a mechanistic viewpoint, it should be noted that the mono‐ or diene insertion into the π‐allyl system of [La]( syn ‐η 3 ‐C 4 H 7 ) occurs directly and in a concerted way. There is no need to form an intermediate σ‐allyl complex;15 this was also reported by Tobisch for Ti‐based catalysts 12c…”
Section: Resultssupporting
confidence: 66%
“…Finally, we have assumed that the catalytically active species is [Cp*(BH 4 )LaR] (R=alkyl or allyl) without considering additional solvent (THF) molecules coordinated to La. In a previous theoretical study, we demonstrated that decoordination of THF to the metal center is thermoneutral for this type of complex 15…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of ES copolymers having syndiotactic styrene–styrene sequences is particularly challenging. Notable recent advances have been obtained with scandium19 and neodymium20, 21 complexes 3. In contrast, the half‐titanocenes active for syndiospecific styrene polymerization exhibit low catalytic activities for ethylene polymerization and ES copolymerization; the resulting polymers are typically reactor blends of polystyrene, polyethylene (PE), and ES copolymer,4, 11, 14, 15, 22–24 although selected aryloxide complexes were reported to be selective for ES copolymerization 25, 26.…”
Section: Introductionmentioning
confidence: 99%